Advancing the Social Epidemiology Mission of the American Journal of Epidemiology. Issue 4 (13th November 2021) - Gilman, Stephen E; Aiello, Allison; Galea, Sandro; Howe, Chanelle J; Kawachi, Ichiro; Lovasi, Gina S; Dean, Lorraine T; Oakes, J Michael; Siddiqi, Arjumand; Glymour, M Maria
Abstract: Social epidemiology is concerned with how social forces influence population health. Rather than focusing on a single disease (as in cancer or cardiovascular epidemiology) or a single type of exposure (e.g., nutritional epidemiology), social epidemiology encompasses all the social and economic determinants of health, both historical and contemporary. These include features of social and physical environments, the network of relationships in a society, and the institutions, politics, policies, norms and cultures that shape all of these forces. This commentary presents the perspective of several editors at the Journal with expertise in social epidemiology. We articulate our thinking to encourage submissions to the Journal that: 1) expand knowledge of emerging and underresearched social determinants of population health; 2) advance new empirical evidence on the determinants of health inequities and solutions to advance health equity; 3) generate evidence to inform the translation of research on social determinants of health into public health impact; 4) contribute to innovation in methods to improve the rigor and relevance of social epidemiology; and 5) encourage critical self-reflection on the direction, challenges, successes, and failures of the field.